2017
DOI: 10.1111/his.13281
|View full text |Cite
|
Sign up to set email alerts
|

MYB,MYBL1,MYBL2 and NFIB gene alterations and MYC overexpression in salivary gland adenoid cystic carcinoma

Abstract: The present study suggests that (1) nearly 90% of AdCCs may have gene alterations of either MYB, MYBL1 or NFIB, suggesting the diagnostic utility of the FISH assay, (2) MYB or MYBL1 gene splits may be associated with local aggressiveness of the tumours and overexpression of MYC, which is one of the oncogenic MYB/MYBL1 targets and (3) MYC overexpression may be a risk factor for disease-free survival in AdCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 46 publications
5
54
0
Order By: Relevance
“…MYBL1 was overexpressed as compared with MYB–NFIB ‐positive AdCCs and the breast cancer cell lines tested, and MYB expression was low (Figures A and B). As in a previously described MYBL1 ‐rearranged salivary gland AdCC , c‐MYB protein expression was observed (Figure A; supplementary material, Figure S2A), potentially caused by cross‐reactivity between the c‐MYB antibody and the rearranged A‐MYB protein, owing to the extensive homology between MYB and MYBL1 and their respective proteins.…”
Section: Resultssupporting
confidence: 73%
“…MYBL1 was overexpressed as compared with MYB–NFIB ‐positive AdCCs and the breast cancer cell lines tested, and MYB expression was low (Figures A and B). As in a previously described MYBL1 ‐rearranged salivary gland AdCC , c‐MYB protein expression was observed (Figure A; supplementary material, Figure S2A), potentially caused by cross‐reactivity between the c‐MYB antibody and the rearranged A‐MYB protein, owing to the extensive homology between MYB and MYBL1 and their respective proteins.…”
Section: Resultssupporting
confidence: 73%
“…Moreover, the presence of the translocation was not associated with AdCC microscopic subtype and the presence of perineural invasion. However, Fujii et al () observed a significant association between MYB/MYBL1 split‐positive cases and positive surgical margins.…”
Section: Resultsmentioning
confidence: 99%
“…Mitani et al () observed that cases carrying MYB alterations were associated with the presence of recurrences and metastases. More recently, Fujii et al () observed that MYB/MYBL1 split‐positive cases were associated with positive microscopic surgical margins, but the authors did not investigate cases carrying only the MYB‐NFIB translocation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, a fusion between the myeloblastosis ( MYB ) and nuclear factor I/B ( NFIB ) genes, resulting from t(6;9)(q22‐23;p24) translocation, was firstly identified in all 11 ACCs studied by Persson et al The fusion was found to be associated with high 5′‐MYB gene expression. MYB is an oncogene, and MYB‐NFIB gene fusion can lead to the activation of MYB and its target genes that are associated with apoptosis, cell cycle control, cell adhesion, growth, differentiation, and angiogenesis, including Proto‐Oncogene Receptor Tyrosine Kinase (KIT) , CD34 Molecule , Baculoviral IAP Repeat Containing 3(BIRC3) , MYC Proto‐Oncogene , and Mitotic Arrest Deficient Like 1 (MAD1L1) . The discovery of MYB gene fusion transcripts has revolutionized the diagnosis, surveillance, and treatment of ACC.…”
Section: Introductionmentioning
confidence: 99%
“…MYB-NFIB gene fusion can lead to the activation of MYB and its target genes that are associated with apoptosis, cell cycle control, cell adhesion, growth, differentiation, and angiogenesis, including Proto-Oncogene Receptor Tyrosine Kinase (KIT), CD34 Molecule, Baculoviral IAP Repeat Containing 3(BIRC3), MYC Proto-Oncogene, and Mitotic Arrest Deficient Like 1 (MAD1L1). [10][11][12] The discovery of MYB gene fusion transcripts has revolutionized the diagnosis, surveillance, and treatment of ACC. Recently, studies have found MYB gene fusion in patients with ACC, and NFIB has been the only consistent gene that rearranges with MYB.…”
Section: Introductionmentioning
confidence: 99%